Thermodynamic, adsorption and corrosion inhibitive behaviour of benzyl nicotinate on cold rolled steel in sulphuric acid solution - Vinutha Rangaswamy Mutugadahalli; Venkatesha Venkatarangaiah Thimmappa (Journal of Electrochemical Science and Engineering, 2015)
The inhibition performance of benzyl nicotinate (BN) on corrosion of cold rolled steel (CRS) in 0.5 M H2SO4 solution has been investigated using weight loss, Tafel polarization and electrochemical impedance spectroscopy (EIS). The BN acts as mixed type inhibitor. The thermodynamic parameters indicate the comprehensive nature adsorption of BN on CRS which obey Langmuir isotherm. Morphological investigation of corrosion inhibition is carried out using AFM and optical microscopic studies support the formation of inhibitor film on CRS. There is a good agreement between the values of weight loss measurements and electrochemical studies.